Investigation of heat stress in workplace for different work groups according to ISO 7243 standard in Mehr Petrochemical Complex, Assaluyeh, Iran - Hemmatjo, Rasool; Zare, Sajad; Babaei Heydarabadi, Akbar; Hajivandi, Abdollah (Archives of Advances in Biosciences, 2013)
Heat stress is a significant occupational health and safety for workers in petrochemical industries. Heat stress is a combination of heat load individual and environmental factors impose on workers’ bodies, which in turn, have impacts on workers’ performance, safety, and health. The present paper is carried out to determine the heat stress levels in workplace and to compare it with allowed Wet Bulb Globe Temperature (WBGT) according to ISO 7243 standard. the present study was carried out in three consecutive weeks in Mehr Petrochemical Complex in South Pars Special Economic Zone in Assaluyeh, 270Km southeast of Bushehr in spring of 2011. The study was carried out on workers in different parts including workers in packaging, mechanics, welding, and store keeping sections. Environmental parameters of dry temperature, natural wet temperature, glowing temperature, and relative humidity were measured to calculate an index for Wet Bulb Globe Temperature according to ISO7243 standard, and metabolism rate was estimated according to ISO 8996 standard. Metabolism level for workers in two groups of mechanics and welding sections according to ISO 8996 standard was 95W/m2, and for workers of packaging and store keeping sections calculated as 75W/m2. Based on ISO 8996, work load for all four sections was light. The means of weather parameters such as dry temperature, natural wet temperature, glowing temperature, and relative humidity were statistically significant for all four sections. It was also indicated that the highest level of WBGT were obtained for workers in mechanics (33.26±0.21), packaging (32.02±0.2), welding (31.37±0.2), and the lowest level was estimated for store keeping workers (27.4±0.22), with changes being statistically significant. DISCUSSION AND CONCLUSION: findings of the present study indicated significant changes between different groups in measured parameters and calculated indices, which confirm results of previous body of research. Workers in three groups of mechanics, packaging, and welding are exposed to heat stress, and among these three, mechanics workers’ exposure to heat stress is higher, but WBGT index in store keeping work place is lower than allowed level. Thus, they have been experiencing favourable work atmosphere.